Actuation and blocking force of carbon nanotube/polymer actuator with platelet-shaped graphene. (17th January 2020) - Monobe, Hirosato; Tsuchiya, Nobuyuki; Yamamura, Masahiro; Mukai, Ken; Sugino, Takushi; Asaka, Kinji
Abstract: Different types of platelet-shaped graphene were used as structural and conductive filler of the carbon nanotube (CNT) porous electrode films of a dry-type polymer actuator consisting of CNT, ionic liquid, and a base polymer to enhance actuation performance. The strain and blocking force were evaluated from the bending motion of the actuator with a frequency response from 10 to 0.005 Hz. Ten types of CNT electrode film were prepared by varying the surface areas and added amounts of the graphene. When the same amount of platelet-shaped graphene (50 mg) as that of CNT (50 mg) was added to the CNT electrode, the generated force became almost twice that of CNT (50 mg) without any graphene additives, while the observed displacement remained a similar value. The addition of platelet-shaped graphene improves the expansion and generated stress of the three-layer actuator consisting of CNT electrodes.